One-stage versus two-stage video-assisted thoracic surgery for synchronous bilateral pulmonary nodules: protocol for a single center, non-randomized clinical trial (OTVATS-1) - Yu Han; Weixun Zhang; Peihang Xu; Zhoujunyi Tian; Yang Hao; Jin Zhang; Tai Ren; Chaoyang Liang (BMC Surgery)
Abstract Background Previous retrospective studies demonstrated both one-stage and two-stage video-assisted thoracic surgery (VATS) for bilateral pulmonary nodules were safe and feasible in selected patients. However, prospective data is still lacking. The purpose of this trial is to prospectively compare the prognostic and perioperative outcomes between one-stage and two-stage VATS for synchronous bilateral pulmonary nodules. Methods We conduct a prospective clinical trial to investigate the surgical outcomes of one-stage and two-stage VATS for patients with synchronous bilateral pulmonary nodules. This trial plan to enroll 198 patients from a single institution during a period of 5 years. The primary outcome is 5-year overall survival. Secondary outcomes include 5-year disease free survival, 3-year overall survival, 3-year disease free survival, overall complications rate, 30-day mortality, pain score after surgery, surgical time, blood loss in the operation, duration of chest tube, length of stay, and quality of life score after surgery. Discussion To our knowledge, this study is the first prospective registered clinical trials to compare the clinical outcomes after one-stage or two-stage VATS for synchronous bilateral non-small cell lung cancer. Trail registration This study underwent review by the Ethics Committee of China-Japan Friendship Hospital under No. 2023-KY-061-1. It has been officially registered with the China Clinical Trial Registry, TRN: ChiCTR2300071198 and registration date is May. 8, 2023.